Cosmology from LOFAR two-metre sky survey data release 2: cross-correlation with the cosmic microwave background - Nakoneczny, Szymon; Alonso, D.; Bilicki, M.; Schwarz, D. J.; Hale, C. L.; Pollo, A.; Heneka, Caroline; Tiwari, P.; Zheng, J.; Brüggen, M.; Jarvis, M. J.; Shimwell, T. W. (Astronomy and astrophysics, 2024)
Aims. We combined the LOw-Frequency ARray (LOFAR) Two-metre Sky Survey (LoTSS) second data release (DR2) catalogue with gravitational lensing maps from the cosmic microwave background (CMB) to place constraints on the bias evolution of LoTSS-detected radio galaxies, and on the amplitude of matter perturbations. Methods. We constructed a flux-limited catalogue from LoTSS DR2, and analysed its harmonic-space cross-correlation with CMB lensing maps from Planck, Cℓgk, as well as its auto-correlation, Cℓgg. We explored the models describing the redshift evolution of the large-scale radio galaxy bias, discriminating between them through the combination of both Cℓgk and Cℓgg. Fixing the bias evolution, we then used these data to place constraints on the amplitude of large-scale density fluctuations, parametrised by σ8. Results. We report the significance of the Cℓgk signal at a level of 26.6σ. We determined that a linear bias evolution of the form bg(z) = bg,D/D(z), where D(z) is the growth rate, is able to provide a good description of the data, and we measured bg,D = 1.41 ± 0.06 for a sample that is flux limited at 1.5 mJy, for scales ℓ < 250 for Cℓgg, and ℓ < 500 for Cℓgk. At the sample’s median redshift, we obtained b(z = 0.82) = 2.34 ± 0.10. Using σ8 as a free parameter, while keeping other cosmological parameters fixed to the Planck values, we found fluctuations of σ8 = 0.75−0.04+0.05. The result is in agreement with weak lensing surveys, and at 1σ difference with Planck CMB constraints. We also attempted to detect the late-time-integrated Sachs-Wolfe effect with LOFAR data; however, with the current sky coverage, the cross-correlation with CMB temperature maps is consistent with zero. Our results are an important step towards constraining cosmology with radio continuum surveys from LOFAR and other future large radio surveys.
Online veröffentlicht: 25. Januar 2024
Gesehen am 28.06.2024